Assessment of free radical scavenging activity and polyphenolic content in leaves of Neurocalyx calycinus (R. Br. ex Benn.) Rob. - a medicinal plant used by Cholanaickan tribe in India - Ajayakumar Lalitha Aneeshkumar; Somasekharan Nair Rajam Suja; Elenjikkal Avarachan Siril; Sreedharan Nair Rajasekharan (Journal of Traditional and Folk Practices (JTFP), 2017)
Neurocalyx calycinus (R. Br. ex Benn.) Rob. is an endemic species of the family Rubiaceae, found in Western Ghats of India and Sri Lanka. The leaf paste of N. calycinus has been used by Cholanaickan tribe as medicine to heal wounds, burns, inflammation and pain. Many of the human diseases are manifested due to the accumulation of free radicals. Plant derived antioxidants have the power to scavenge these free radicals without any internal complications. Aqueous, n-hexane, chloroform, ethyl acetate and ethanol extracts of the leaves of N. calycinus were selected for qualitative phytochemical screening. DPPH, nitric oxide, superoxide and hydroxyl radical scavenging assays were carried out. Total phenolic, flavonoid and antioxidant content of all the extract was measured. Phytochemical screening showed that alkaloids, steroids, phenolic compounds, glycosides and saponins were found in the ethanolic extract. Ethanol extract showed better antioxidant activity than the other solvent extracts. The reducing power of all the extracts was increased dose dependently. Highest amount of phenolic (56.27 mg of gallic acid equivalent /gm of dried extract), flavonoid (36.92 mg of quercetin equivalent /gm of dried extract) and antioxidant (85.68 mg of ascorbic acid equivalent/gm of dried extract) content was found in the ethanolic extract. A positive correlation (R2) was found between the total phenolic content and free radical scavenging activity of the leaf extract of N. calycinus. The results confirmed that the phenolic compounds in the ethanolic extract of the leaves of N. calycinus are potent source of natural antioxidants.